TELENURSING FOR CARING PATIENTS INFECTED WITH CORONAVIRUS 2019 WHO ENTERED TO HOME ISOLATION SYSTEM: NURSE’S ROLE - Boonyaratkalin, Panisa (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
Coronavirus disease 2019 is a disease that can spread easily. Once infected, the patient has a chance of developing severe complications, up to death. The situation of Coronavirus disease 2019 has become more severe but the resources for treatment at the hospital are limited, including medical personnel, number of beds, medicines, and other supplies. The management of the Coronavirus disease 2019 epidemic situation in Thailand has therefore encouraged the management of patients who have asymptomatic or mild symptoms to stay at home, starting from the end of the year 2020. After registering into the system, patients will be advised how to self-isolate at home, manage symptoms, and observe unusual symptoms that urge the patient to come to the hospital. They will be tracked by the telehealth system until the due date of isolation. In addition, Patient Under Investigation (PUI) is also a group that has to isolate themselves at home and requires a telehealth system likewise. Nurses are health care professionals who play a key role in managing the care of patients by using telenursing, reducing the incidence of complications, mortality, and the spread of infection in the community, and keeping the Thai public health system to be able to adequately manage hospitals for severely ill patients.